Rancang Bangun Sistem Informasi Bank Sampah Berbasis Web - Yustanti, Martina Indah; , Hermawan Sulistyanto,ST.,M.T (2017)
Trash is waste material resulting from a production process both industry and house hold. It is necessary to address the handling to overcome problems arising from waste, one of them is the presence of the Bank Sampah. In data processing in Bank Sampah is still done manually recording with books. Therefore, along with the rapid advances in technology created a web-based system that can help a process transaction in Bank Sampah. In the process of making system do the research in Bank Sampah Asri Raharjo Pati Distric, Pati Regency. The research use a waterfall method as system development method. Where as in the collection of data, the writer used a survey method, interview, literature, documentation and archives. The result of the research is a system information web-based that helps the officers in serving transaction and customer can check the balance on their own.